Review on success factors of waqf information management system in Malaysia - Norjansalika Janom; Mohd Zairul Izham; Fairuz Suraya Mansor; Syaripah Ruzaini Syed Aris; Nor Shahniza Kamal Bashah; Noor Habibah Arshad (Institute of Advanced Engineering and Science, 2019)
Waqf is one of the important economic instruments in Islam. Waqf is known as an endowment consist of donating a building, a sum of money or plot of land for charitable purposes. Various relevant aspects with the field of waqf have been studied and debated by scholars in the area of socio-political studies, economic, accounting as well as waqf information management system development. Current research findings have shown few glaring issues in terms of the difficulty to distribute waqf benefits caused by incomplete file information, transparency of waqf documentation, lack of detailed information about waqf assets and the requirements to provide timely and sufficient information to the related stakeholders. Thus, this study explores conceptual model of integrated success factors of Waqf information management system from few literature analysis. The conceptual success model that consists of activities, relationships, relative advantage, compatability, triability, image, visibility, result demonstrability, voluntariness, complexity and trust have been used to demonstrate the Islamic and technology concepts of waqf information system. Thorough review from several research works will help to understand the gaps in the information system management related to the state waqf agencies in Malaysia. The findings of the above issues prove on the need to identify the success factors of waqf information system management thus, helps to ensure the success development of the system. The findings should be of great interest to both researchers and practitioners.